Investigation on sound absorption of rice-husk reinforced composite - Mahzan, Shahruddin
Natural fibres have become an important element in producing alternative fibrereinforced composites. The use of natural fibre for sound absorber material has recently investigated. This study investigates the use of rice-husk waste as the potential element for sound absorption material of rice-husk reinforced composite. The rice husk is initially cleaned and dried up at room temperature (25 - 30 ºC). The dried rice husk is then mixed together with Polyurethane (PU) foam as a binder to produce the rice husk reinforced composite. Six different samples have been produced according to the percentage of rice husk. The specimens were tested using an impedance tube. The result found that the best percentage of rice husk was obtained at 25 percents. The sound absorption coefficient obtained demonstrated that the mixture produced the best performance at low frequency region. The results also demonstrated that the rice husk reinforced composite have a better sound coefficient compared to other natural materials, hence promising a great potential for commercialisation.